Psychophysiological profile and prediction equations for technical performance of football players - Vaz,Marcelo S. (2019)
Abstract The objective was to correlate specific technical skills (STS) with the psychophysiological performance. STS from 15 soccer athletes were collected by technical scouting of two matches. Countermovement jump, blood concentration of creatine kinase ([CK]), heart rate variability (HRV) and the scores of DALDA and POMS were also obtained 24 h after both matches. Predictive equations were elaborated, and POMS and DALDA scores were the only variables which fits the models for STS with high coefficient of determination (r2) for finalization (r2 = 0.85), interception (r2 = 0.73), pass right (r2 = 0.32), tackling (r2 = 0.69) and loss of ball (r2 = 0.35). The psychological variables identified through POMS and DALDA have shown greater influence on the STS.